The speed of the internationalisation process and the institutional networks of family SMEs in the DOC Rioja wine industry - Marta Fernández Olmos; Giulio Malorgio (Wine Economics and Policy, 2020)
Institutional networking is a key element in businesses' internationalisation processes and is an important strategy for promoting the long-term growth and survivability of family SMEs in the DOC Rioja wine industry. We hold that the proportion of family members in the TMT plays an important role in strategic decision-making and helps to explain the speed of their internationalisation process. This paper contributes to the scant research on the influence of family involvement in the TMT by analysing the moderating effects of two diversities on the relationship between institutional networking and the speed of internationalisation: the family TMT ratio and generational involvement. Using a broad sample of 77 family wineries in DOC Rioja, the results obtained indicate that institutional networking plays a significant role in explaining the speed of internationalisation in family firms and that this relationship is weaker when a larger proportion of family members serve as top managers. The empirical results also have interesting implications for the managers of family firms as it may help them to identify the effective composition of TMTs to be considered when deciding on the process of internationalisation.
Keywords: 330; institutional networking; speed of internationalisation; DOC Rioja wine